Inventory of transitions on sea dikes at the German coast: spatial analysis, design and damages - Schulte, Ina; Rodermund, Henrike; Selvam, Harish; Becker, Jessica; Schweiger, Constantin; Schürenkamp, David; Goseberg, Nils; Schüttrumpf, Holger (Frontiers in Built Environment, 2024)
German coastal areas are often protected from flood events by a primary sea dike line of more than 1,200 km. Many transition areas, such as the change of surface covering materials and other dike elements such as stairs, fences, or ramps at intermittent locations, characterize the stretch of this sea dike line. During storm surges and wave overtopping, the onset of damage, especially dike cover erosion, is often initiated at these transitions due to locally disturbed flow characteristics, increased loads, and reduced strength at the interface. An in-depth understanding of damage initiation and building stock conditions along coastlines as a foundational element of a flood cycle is essential in order to accurately assess existing defense structures, both deterministically and probabilistically. Thus, the present study is motivated to examine the variety of transition areas on the sea dikes along the German coasts, for further assessment of probability of their damage and failure. A novel remote inventory was elaborated manually, based on satellite images for a length of 998 km along the German North Sea and 123 km along the German Baltic Sea coast and estuaries, and it shows the spatial distribution and frequency of such transitions on sea dikes. During additional on-site investigations at different locations at the coast, detailed information about design variants of dike elements as well as damage to transitions were recorded and reported systematically. The results of the on-site investigations allow the development of a damage catalog in relation to transitions and the validation and verification of the remote inventory. By categorizing and spatially analyzing a large number of transitions (n ≈ 18,300) and damages along the coast, particularly vulnerable transitions and hot spots of loading can be further investigated regarding the flow-structure-soil interaction. Through this, structural layouts and material combinations can be optimized for the design of sea dikes.